Empowering health literacy in dialysis care: bridging the gap with patient-oriented education - Ibrahim, Norkasihan (Faculty of Pharmacy, 2025)
Living with end-stage kidney disease (ESKD) and undergoing haemodialysis is a lifelong journey requiring discipline, understanding, and active participation in care. For many patients, navigating complex medication regimens, strict dietary restrictions, and multiple comorbidities can be overwhelming. Without adequate health literacy, these challenges often translate into missed dialysis sessions, poor adherence to treatment, frequent hospital visits, and diminished quality of life. This session empowering patients to take ownership of their health through accessible, practical, and culturally relevant education.